Knives
By distributing hard particles like tungsten carbide or titanium carbide on the cutting edge with a specific Rq/A ratio, the sharpness and durability of cutlery are enhanced, addressing the wear issues of iron-based metals.
Patent Information
- Application Number
- JP2021021491
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-23
- Filing Date
- 2021-02-15
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2041-02-15
AI Technical Summary
Cutlery made from iron-based metals, such as steel, faces issues with sharpness due to low hardness, leading to rapid wear and poor long-lasting sharpness.
Distributing hard particles, such as tungsten carbide or titanium carbide, on the cutting edge with a specific Rq/A ratio of 0.1≦Rq/A≦2.5, bonded by a metal phase containing an iron group element, enhances sharpness and durability.
The solution results in cutlery with improved sharpness and durability by maintaining the cutting edge's effectiveness over time.
Smart Images

Figure 0007610425000003 
Figure 0007610425000004 
Figure 0007610425000001
Abstract
Description
[Technical Field]
[0001] The present disclosure relates to cutting tools. [Background technology]
[0002] BACKGROUND ART Steel knives are widely used in ordinary homes, restaurants, cafeterias, etc. (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2000-189682 Summary of the Invention [Problem to be solved by the invention]
[0004] The performance required for blades such as kitchen knives is sharpness and durability of the sharpness. Blades made primarily of iron-based metals such as steel, as shown in Patent Document 1, often have an extremely sharp cutting edge to enhance sharpness. However, due to their low hardness, the cutting edge is prone to wear, resulting in a problem of poor durability of the sharpness. The present disclosure has been made in view of the above circumstances, and aims to provide a blade that has both good sharpness and durability of the sharpness. The present disclosure can be realized in the following forms. [Means for solving the problem]
[0005] [1] A blade having hard particles distributed at least on the cutting edge, The root mean square height Rq (μm) of the cutting edge and the crystal grain size A (μm) of the hard particles are A cutting tool that satisfies 0.1≦Rq / A≦2.5. [Effects of the Invention]
[0006] The blade of the present disclosure has excellent sharpness and durability of the sharpness. [Brief explanation of the drawings]
[0007] [Figure 1] FIG. 1 is a plan view of an example of a kitchen knife. [Figure 2] FIG. 1 is an explanatory diagram showing a method for testing knives. DETAILED DESCRIPTION OF THE INVENTION
[0008] Here, a preferred example of the present disclosure will be described. [2] The blade according to [1], wherein at least a portion of the hard particles are tungsten carbide particles.
[0009] [3] The cutting tool according to [1] or [2], wherein at least a portion of the hard particles are one or more types of particles selected from titanium carbide and titanium carbonitride.
[0010] [4] At least at the cutting edge, the hard particles are bonded by a metal phase, The blade according to any one of [1] to [3], wherein the metal phase contains an iron group element.
[0011] [5] A blade described in any one of [1] to [4], which is a kitchen knife.
[0012] The present disclosure will be described in detail below. In this specification, when a numerical range is indicated using "to" it is intended to include both the lower limit and the upper limit unless otherwise specified. For example, the expression "10 to 20" includes both the lower limit "10" and the upper limit "20". In other words, "10 to 20" has the same meaning as "10 or more and 20 or less".
[0013] A kitchen knife 1 is shown as an example of a blade in this embodiment (see FIG. 1). The kitchen knife 1 has a blade 3 and a handle 9. The blade 3 has a cutting edge 5 with a blade attached. The tip of the cutting edge 5 is called the cutting edge 7 and is used for cutting thin ingredients into small pieces. The part of the cutting edge 5 closest to the handle 9 is called the blade base 11 and is used for delicate tasks such as peeling. The end of the cutting edge 5 on the handle 9 side of the blade base 11 is called the jaw 13 and is used for removing sprouts from potatoes, for example. The back of the knife 1, that is, the back of the blade 3, is a ridge 15, which is used as a part to hold with the hand and also for removing scales, etc.
[0014] The kitchen knife 1 has hard particles distributed at least on the cutting edge 5. The hard particles may be distributed over the entire blade 3. When hard particles are distributed on the cutting edge 5, the durability of the sharpness can be improved. The distribution of the hard particles is not particularly limited, but it is preferable that at least some of the hard particles are exposed on the surface of the cutting edge 5 .
[0015] In the knife 1, the root mean square height Rq (μm) of the cutting edge 5 and the crystal grain size A (μm) of the hard particles satisfy 0.1≦Rq / A≦2.5. From the viewpoint of improving sharpness, Rq / A is preferably 0.5 or more, and more preferably 0.7 or more. From the viewpoint of improving the durability of sharpness, Rq / A is preferably 2.0 or less, and more preferably 1.5 or less. From these viewpoints, it is more preferable that the knife 1 satisfies 0.5≦Rq / A≦2.0, and even more preferably 0.7≦Rq / A≦1.5.
[0016] The root mean square height Rq of the cutting edge 5 is measured as follows. A surface profile measuring device (INFINITE FOCUS, manufactured by ALICONA) can be used for the measurement. First, the sharpened blade 3 is set with the cutting edge 5 facing upward. After scanning 300 μm of the cutting edge 5 in the direction of extension of the cutting edge 5, a cross-sectional roughness analysis is performed to measure the root mean square height. This measurement is performed at five locations spaced apart in the direction of extension of the cutting edge 5, and the average value is calculated as the root mean square height Rq of the cutting edge 5. The Rq calculated in this way serves as an index for evaluating the degree of unevenness (zigzag) of the contour of the cutting edge 5 when viewed from the thickness direction of the blade 3. There is no particular limitation on the root mean square height Rq of the cutting edge 5. The root mean square height Rq of the cutting edge 5 can be, for example, 0.1 μm or more and 2.4 μm or less. The root mean square height Rq of the cutting edge 5 can be adjusted by changing the grindstone grain size and grindstone rotation speed during sharpening.
[0017] The crystal grain size A of the hard particles is measured as follows: A 10 mm square test piece is cut out from any point on the cutting edge 5 using a wire electric discharge machine. The test piece is mirror-polished, then etched, and an image is taken at 10,000x magnification using a field emission scanning microscope (FE-SEM). The crystal grain size of the hard particles is determined using the intercept method in a 25 μm square region in the obtained image. Images are taken at any five points, and the average value is taken as the crystal grain size A of the hard particles. The crystal grain size A of the hard particles is not particularly limited and can be, for example, 0.4 μm or more and 2.0 μm or less. The crystal grain size A of the hard particles can be adjusted by changing the material used for the cutting edge 5.
[0018] When Rq / A is 0.1 or more and 2.5 or less, the hard particles are suitably arranged on the convex portions of the uneven (zigzag) shape of the cutting edge 5, increasing the contact area between the cutting edge 5 (hard particles) and the workpiece, thereby improving sharpness. Because the hard particles are harder than steel and the like, the sharpness can be maintained for a long time. If Rq / A is less than 0.1, the cutting edge becomes smooth and the contact area decreases, resulting in a decrease in sharpness. If Rq / A exceeds 2.5, the protrusions become larger, the resistance from the object to be cut increases, and the protrusions break off (wear) with use, reducing the contact area, which results in a decrease in the durability of the sharpness.
[0019] The hard particles may be, for example, one or more particles selected from WC (tungsten carbide), TiC (titanium carbide), TiN (titanium nitride), TiCN (titanium carbonitride), TaC (tantalum carbide), Cr3C2 (chromium carbide), Mo2C (molybdenum carbide), and VC (vanadium carbide). At least a portion of the hard particles are preferably tungsten carbide particles. Tungsten carbide is a highly hard material, and by including tungsten carbide particles as the hard particles, the durability of the sharpness is suitably improved. At least a portion of the hard particles are preferably one or more particles selected from titanium carbide and titanium carbonitride. Titanium carbide and titanium carbonitride are high-hardness materials, and by including one or more particles selected from titanium carbide and titanium carbonitride as hard particles, the durability of sharpness is suitably improved. In addition to tungsten carbide particles, titanium carbide particles, and titanium carbonitride particles, the effect of improving the durability of sharpness has also been confirmed for titanium nitride particles, tantalum carbide particles, chromium carbide particles, molybdenum carbide particles, and vanadium carbide particles.
[0020] In the knife 1, at least at the cutting edge 5, the hard particles are bonded by a metal phase, and the metal phase preferably contains an iron group element. The iron group elements are Fe (iron), Co (cobalt), and Ni (nickel). The inclusion of an iron group element improves the effect of absorbing impacts from food ingredients and makes it difficult for the protrusions to chip. As a result, the durability of the sharpness can be suitably improved.
[0021] Cemented carbide can be used as a material for such a kitchen knife 1. As the cemented carbide, a cemented carbide containing tungsten carbide crystal particles (hereinafter also referred to as "tungsten carbide (WC)-based cemented carbide") is preferable. Examples of tungsten carbide based hard alloys include WC-Ni based hard alloys, WC-Co based hard alloys, WC-Fe based hard alloys, WC-Ni-Cr based hard alloys, and WC-Co-Cr based hard alloys. The content of the binder phase (metal phase) in a tungsten carbide-based cemented carbide is not particularly limited. When the entire tungsten carbide-based cemented carbide is taken as 100 volume %, the content of the binder phase is preferably 8 volume % to 40 volume %. Here, the "binder phase" means "Ni" in a WC-Ni-based cemented carbide, "Co" in a WC-Co-based cemented carbide, "Fe" in a WC-Fe-based cemented carbide, "Ni-Cr" in a WC-Ni-Cr-based cemented carbide, and "Co-Cr" in a WC-Co-Cr-based cemented carbide. Furthermore, WC-Ni based cemented carbide and WC-Ni-Cr based cemented carbide are preferred from the viewpoint of being highly corrosive to acids and alkalis and ensuring that the sharpness of the knife 1 lasts longer. In the case of a WC-Ni-Cr based cemented carbide, it is preferred that the binder phase is a Ni-based alloy. That is, when the "Ni-Cr" as the "binder phase" is taken as 100% by volume, it is preferred that the "Ni" content is more than 50% by volume. Furthermore, it is preferred that the "Cr" content is 1% to 10% by volume for 100% by volume of the "Ni-Cr" as the "binder phase," with the remainder being "Ni."
[0022] Specific examples of the cemented carbide alloy that is the material of the knife 1 include "NF30," "NF40," "NF50," "NF60," "NF70," and "VF70" in CIS (Cemented Carbide Tool Association Standard) 019D-2005. Furthermore, cemented carbide alloys of the same grade that differ from these cemented carbide alloys in at least one of the following characteristics may also be used: binder phase material, hard particle material, hard particle size, and hardness.
[0023] Cermet can be used as a material for the knife 1. As the cermet, a cermet containing one or more types of particles selected from titanium carbide and titanium carbonitride (hereinafter also referred to as "TiC-based cermet" or "TiCN-based cermet") is preferable. Examples of TiC-based cermets include TiC-Ni-based cermets, TiC-Co-based cermets, TiC-Fe-based cermets, TiC-Cr3C2-Ni-based cermets, and TiC-Mo2C-Ni-based cermets. The content of the binder phase (metal phase) in TiC-based cermets is not particularly limited. When the entire TiC-based cermet is taken as 100 volume %, the content of the binder phase is preferably 8 volume % to 40 volume %. Here, the "binder phase" means "Ni" in TiC-Ni-based cermets, "Co" in TiC-Co-based cermets, "Fe" in TiC-Fe-based cermets, "Ni" in TiC-Cr3C2-Ni-based cermets, and "Ni" in TiC-Mo2C-Ni-based cermets. Examples of TiCN-based cermets include TiCN-Ni-based cermets, TiCN-Co-based cermets, TiCN-Fe-based cermets, TiCN-Cr3C2-Ni-based cermets, and TiCN-Mo2C-Ni-based cermets. The content of the binder phase (metal phase) in TiCN-based cermets is not particularly limited. When the entire TiCN-based cermet is taken as 100 volume %, the content of the binder phase is preferably 8 volume % to 40 volume %. Here, the "binder phase" means "Ni" in TiCN-Ni-based cermets, "Co" in TiCN-Co-based cermets, "Fe" in TiCN-Fe-based cermets, "Ni" in TiCN-Cr3C2-Ni-based cermets, and "Ni" in TiCN-Mo2C-Ni-based cermets. Furthermore, from the viewpoint of having excellent corrosion resistance against acids and alkalis and allowing the sharpness of the knife 1 to last longer, TiC-Ni based cermets, TiC-Cr3C2-Ni based cermets, TiC-Mo2C-Ni based cermets, TiCN-Ni based cermets, TiCN-Cr3C2-Ni based cermets, and TiCN-Mo2C-Ni based cermets are preferred.
[0024] Specific examples of cermets that are the material of the knife 1 include those in which the type of hard particles in "NF30," "NF40," "NF50," "NF60," "NF70," "NF80," and "NM70" in CIS (Cemented Carbide Tool Association Standard) 019D-2005 has been replaced with one or more types selected from titanium carbide and titanium carbonitride instead of tungsten carbide. In the present disclosure, for example, a cermet that has the same type of metal phase, hard particle content, particle size, etc. as "NF30" and whose hard particles are titanium carbide or titanium carbonitride is also referred to as "equivalent to NF30." [Example]
[0025] The following provides a more detailed explanation using experimental examples. In the tables, when an "*" is added, such as "5*," it indicates that the result is a comparative example. Experimental Examples 1-4, 6-11, 13, and 14 are working examples, and Experimental Examples 5, 12, and 15 are comparative examples. Experimental Examples 16-19, 21-23, and 25-27 are working examples, and Experimental Examples 20 and 24 are comparative examples.
[0026] 1. Making a knife For Experimental Examples 1-14, knives were produced with blades formed from the materials listed in Table 1. The "Hard Particles" column in Table 1 indicates the type of hard particles. The "Metallic Phase" column indicates the type of metallic phase. The "Remarks" column indicates the composition and grade of the material in CIS 0190D-2005. The "VF70 Equivalent" in Experimental Example 14 indicates that the material is the same as VF70 except that the metallic phase is iron. The materials of Experimental Examples 1-14 were made by bonding tungsten carbide particles as hard particles with the metal phases listed in Table 1. The rough shape of the blade was cut out from the base material of these materials using a wire electric discharge machine, and then ground to the desired thickness using a surface grinder.
[0027] For Experimental Examples 16-27, knives were produced with blades formed from the materials listed in Table 2. The "Hard Particles" column in Table 2 indicates the type of hard particles. The "Metallic Phase" column indicates the type of metallic phase. The "Remarks" column indicates that, except for the type of hard particles, the composition and grade of the material are the same as those listed in the CIS 0190D-2005 symbol. The materials of Experimental Examples 16-27 were prepared by bonding titanium carbide particles or titanium carbonitride particles as hard particles with the metal phases listed in Table 2. The rough shape of the blade was cut out from the base material of these materials using a wire electric discharge machine, and then ground to the desired thickness using a surface grinder.
[0028] The polished material was sharpened using a blade grinder. During sharpening, the cutting edge shape was controlled by changing the coarseness of the grinding stone (grit size) and the grinding stone rotation speed (rpm). The polishing conditions are shown in Table 1. The grindstone grain size (#) listed in Table 1 is the grain size according to JIS R 6001-2:2017.
[0029] In Experimental Example 15, a commercially available kitchen knife made of molybdenum vanadium steel was prepared.
[0030] [Table 1]
[0031] [Table 2]
[0032] 2. Evaluation of the physical properties of knives For Experimental Examples 1-14 and Experimental Examples 16-27, the root mean square height Rq (μm) and the crystal grain size A (μm) of the hard particles were measured by the methods described above, and Rq / A was calculated. In each Experimental Example, the root mean square height Rq was adjusted in the range of 0.1 μm to 2.4 μm, and the crystal grain size A of the hard particles was adjusted in the range of 0.4 μm to 2.0 μm. The calculated Rq / A values are shown in the "Rq / A" column in Table 1. Note that, since Experimental Example 15 did not contain hard particles, Rq / A was not calculated and was entered as "-".
[0033] 3. Testing method for knives (evaluation method) (1) Test method for sharpness and durability of sharpness The obtained knives were evaluated for "sharpness before use" and "sharpness after use" using a sharpness tester. A stack of 7.5 mm wide stacks of paper equivalent to newspaper was used as the object to be cut, and the knife was moved back and forth to cut the stack of paper with a pressing load of 8 N between the knife and the stack of paper, a reciprocating width of 10 mm, and a reciprocating speed of 40 mm / s (i.e., two reciprocating strokes per second). Figure 2 shows the knife 1, cutting edge 5, and stack of paper 21 during the test. Each item was evaluated as follows: Sharpness before use: Cutting depth (mm) when an unused knife is moved back and forth once. · Sharpness after use: Cutting depth (mm) in the last stroke when the total cutting depth reaches 1,000 mm.
[0034] (2) Test results for sharpness and durability of sharpness The test results are shown in Tables 1 and 2. The sharpness was evaluated as follows: a knife with a pre-use sharpness of 2.0 mm or more was evaluated as having good sharpness. Furthermore, a knife with a pre-use sharpness of 2.5 mm or more was evaluated as having better sharpness, and a knife with a pre-use sharpness of 3.0 mm or more was evaluated as having particularly good sharpness. The durability of sharpness was evaluated as follows: A knife with a small difference between the sharpness before and after use, a guideline being a difference of 1 mm or less, was evaluated as a good knife.
[0035] For each example, the fulfillment status of the following requirements will be explained. Experimental Examples 1-4, 6-11, 13, and 14 fulfill the following requirements (a), (b), and (d). Experimental Examples 16-19, 21-23, and 25-27 fulfill the following requirements (a), (c), and (d). Experimental Examples 5 and 12 fulfill the following requirements (b) and (d), but do not fulfill requirement (a). Experimental Examples 20 and 24 fulfill the following requirements (c) and (d), but do not fulfill requirement (a). Experimental Example 15 fulfills none of the following requirements (a), (b), (c), and (d). Requirement (a): Hard particles are distributed on the cutting edge, and 0.1≦Rq / A≦2.5 is satisfied. Requirement (b): At least a part of the hard particles are tungsten carbide particles. Requirement (c): At least a part of the hard particles is one or more types of particles selected from titanium carbide and titanium carbonitride. Requirement (d): The hard particles are bound by a metal phase, and the metal phase contains an iron group element.
[0036] Experimental Examples 1-4, 6-11, 13, and 14, which satisfied requirements (a), (b), and (d), had a pre-use sharpness of 2.0 mm or more, and the difference between the pre-use sharpness and the post-use sharpness was 1 mm or less. Experimental Examples 16-19, 21-23, and 25-27, which satisfied requirements (a), (c), and (d), had a pre-use sharpness of 2.0 mm or more, and the difference between the pre-use sharpness and the post-use sharpness was 1 mm or less. In other words, Experimental Examples 1-4, 6-11, 13, 14, 16-19, 21-23, and 25-27 had good sharpness and good sharpness retention.
[0037] Experimental Examples 6-11 were compared, using the same material but with different Rq / A ratios. Experimental Examples 6-11 showed improved sharpness as the Rq / A ratio increased. Among Experimental Examples 6-11, Experimental Examples 8-11, which had an Rq / A ratio of 1.0 or more, showed a smaller difference between sharpness before and after use as the Rq / A ratio decreased, demonstrating good durability of sharpness.
[0038] In contrast, in Experimental Examples 5, 12, 15, 20, and 24, which did not satisfy requirement (a), the sharpness before use was less than 2.0 mm, or the difference between the sharpness before use and the sharpness after use was large. Experimental Example 5 satisfied requirements (b) and (d), but did not satisfy requirement (a) because Rq / A was 0.05. Experimental Example 20 satisfied requirements (c) and (d), but did not satisfy requirement (a) because Rq / A was 0.05. Experimental Examples 5 and 20 had Rq / A of less than 0.1, and therefore did not have good sharpness. Experimental Example 12 satisfied requirements (b) and (d), but did not satisfy requirement (a) because its Rq / A was 3.0. Experimental Example 24 satisfied requirements (c) and (d), but did not satisfy requirement (a) because its Rq / A was 3.0. Experimental Examples 12 and 24 had Rq / A exceeding 2.5, and although the sharpness before use was high, there was a large difference between the sharpness before use and the sharpness after use, and the sharpness did not last long. Experimental Example 15 does not satisfy all of the requirements (a), (b), (c), and (d). Experimental Example 15 did not contain a hard material, and therefore did not maintain its sharpness for long.
[0039] 4. Summary of experimental results By distributing hard particles on the cutting edge and satisfying 0.1≦Rq / A≦2.5, both the sharpness and durability of the sharpness were improved. When at least a part of the hard particles were tungsten carbide particles, the durability of the sharpness was favorably maintained. When at least a part of the hard particles were one or more types of particles selected from titanium carbide and titanium carbonitride, the sharpness was maintained to a satisfactory degree. When the hard particles were bound by a metal phase and the metal phase contained an iron group element, the durability of the sharpness was favorably maintained. It was confirmed that such a blade is suitable as a kitchen knife.
[0040] The present disclosure is not limited to the above-described embodiments, and various modifications and variations are possible within the scope of the claims of the present disclosure.
[0041] (1) In the above embodiment, the blade is a kitchen knife. However, the blade may be a blade other than a kitchen knife, such as a peeler. (2) In addition to the above embodiment, only the cutting edge may be made of the above material, and the rest of the blade may be made of a material that does not contain hard particles. (3) In addition to the above embodiment, the hard particles may be bonded by a metal phase that does not contain an iron group element, such as aluminum. (4) In the above embodiment, a handle that is a separate member from the blade is provided at the base end of the ridge of the blade, but a handle made of a separate member is not essential. For example, the base end of the blade may be processed to function as a handle that can be held by hand. [Explanation of symbols]
[0042] 1...Knife (cutlery) 3...blade 5...Cutting edge 7... Tip 9...Pattern 11...Blade base 13...chin 15...mine
Claims
1. A blade having hard particles distributed at least on the cutting edge, At least a part of the hard particles are tungsten carbide particles or one or more types of particles selected from titanium carbide and titanium carbonitride, The crystal grain size A of the hard particles is 0.4 μm or more and 2.0 μm or less, The cutting edge is made of at least a cemented carbide or a cermet, and the hard particles are bonded to each other by a metal phase at the cutting edge; the metallic phase contains an iron group element; The root mean square height Rq (μm) of the cutting edge and the crystal grain size A (μm) of the hard particles are A blade that satisfies 0.7≦Rq / A≦2.
5.
2. 2. The knife according to claim 1, which is a kitchen knife.
Citation Information
Patent Citations
Cutter and cutter machining method
CN111203919A
Kitchen knife
JP2000189682A
Cutter
JP2018008074A
Blade using ultra-hard microscopic particles
US20090241352A1
Knife and blade finishing method
WO2016035488A1